Efficient bloch‐siegert B1+ mapping using spiral and echo‐planar readouts. Issue 6 (7th February 2013) - Saranathan, Manojkumar; Khalighi, Mohammad Mehdi; Glover, Gary H.; Pandit, Prachi; Rutt, Brian K.
<x xml:space="preserve">Abstract</x> The Bloch‐Siegert (B‐S) B1+ mapping technique is a fast, phase‐based method that is highly SAR limited especially at 7T, necessitating the use of long repetition times. Spiral and echo‐planar readouts were incorporated in a gradient‐echo based B‐S sequence to reduce specific absoprtion rate (SAR) and improve its scan efficiency. A novel, numerically optimized 4 ms B‐S off‐resonant pulse at + 1960 Hz was used to increase sensitivity and further reduce SAR compared with the conventional 6 ms Fermi B‐S pulse. Using echo‐planar and spiral readouts, scan time reductions of 8–16 were achieved. By reducing the B‐S pulse width by a factor of 1.5, SAR was reduced by a factor of 1.5 and overall sensitivity was increased by a factor of 1.33 due to the nearly halved resonance offset of the new B‐S pulse. This was validated on phantoms and volunteers at 7 T. Magn Reson Med 70:1669–1673, 2013. © 2013 Wiley Periodicals, Inc.